Long-term impact of childhood hepatitis B vaccination programs on prevalence among Aboriginal and non-Aboriginal women giving birth in Western Australia. Issue 23 (31st May 2018) - Reekie, J.; Kaldor, J.M.; Mak, D.B.; Ward, J.; Donovan, B.; Hocking, J.S.; Preen, D.; Liu, B.
Highlights: We examined HBV infant and child vaccine program impact on HBVprevalence in adults. In Western Australia, HBV prevalence in Aboriginal women has fallen significantly. Despite the declining prevalence, considerable disparities in HBV prevalence remain. Abstract: Background/Aims: To evaluate the long-term effect of infant and childhood hepatitis B (HBV) vaccination programs among birthing women in Western Australia. Methods: A cohort of Western Australian women born from 1974 to 1995 was created using Birth Registrations and Electoral Roll records. They were linked to a perinatal register and notifiable diseases register to identify women having respectively their first births between 2000 and 2012 and diagnoses of HBV infections. HBV prevalence was estimated in Aboriginal and non-Aboriginal women, and according to maternal birth year cohorts. Results: Of 66, 073 women, 155 (0.23%) had a linked non-acute HBV notification. HBV prevalence was five times higher in Aboriginal women compared to their non-Aboriginal counterparts (0.92%, 95%CI 0.65–1.18 versus 0.18%, 0.15–0.21). Among Aboriginal women, after adjusting for year of giving birth and region of residence, those born in the targeted infant and school-based vaccination era (maternal year of birth 1988–1995) had an 89% lower risk (adjusted odds ratio [aOR] 0.11, 0.04–0.33) of HBV than those born in the pre-vaccination era (1974–1981). Prevalence also differed between Aboriginal women residing in rural/remote areas compared to those in major cities (aOR 3.06, 1.36–6.88). Among non-Aboriginal women, no significant difference in HBV prevalence was observed by maternal birth cohort (p = 0.20) nor by residence (p = 0.23), but there were significant differences by ethnicity with a 36-fold higher prevalence (aOR 36.08, 22.66–57.46) in non-Caucasian versus Caucasian women. Conclusions: A significant decline in HBV prevalence in Aboriginal birthing mothers was observed following the introduction of HBV vaccination programs in Western Australia. There were also considerable disparities in prevalence between women by area of residence and ethnicity. Our findings reflect those observed in women in other Australian jurisdictions. Continued surveillance of HBV prevalence in birthing mothers will provide ongoing estimates of HBV vaccination program impact across Australia and the populations most at risk of chronic HBV.